USING GAUGING IN NONLINEAR PROBLEMS OF ECONOMICS, PHYSICS AND TECHNOLOGY - Badalian, L.H.; Krivorotov, V.F. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2015)
The approach proposed in this paper uses ideas and instruments of gauging theory to handle nonlinear problems in economics, nonlinear dynamics and various technological issues. We see nonlinearity of gauging as hardly a technical issue arising while solving the variation problem, but a structural feature of an intrinsically nonlinear space shaped by its gauge-based connections. Under these assumptions, the solution of the variation problem is shown as invariant to transformations of the vector field which present the initial source of nonlinear disturbances.
Keywords: Cristoffel symbols, economic dynamics, Gauge theory, Solow model, invariant transformations, parallel transport, Cobb–Douglas function, “Invisible Hand”